EARLY INTERVENTION FOR INFANTS WITH DIAGNOSIS OR HIGH RISK OF CEREBRAL PALSY: LITERATURE REVIEW (Movimenta (ISSN 1984-4298), 2023)
Objective: to carry out an integrative literature review to identify and describe the main contemporary early intervention programs for infants diagnosed with or at high risk of cerebral palsy. The dosage, frequency and components of the early intervention programs identified in the review were described. Methods: The searches were carried out in the Pubmed, Cochrane and Pedro databases, from December 2021 to March 2022. The descriptors used were “cerebral palsy”, “early intervention” and “high risk”, in Portuguese and English. Results: Ten (10) articles were included in the study, including five randomized clinical trials, four systematic reviews and one clinical practice guideline. The programs found involved Goals Activity and Motor Enrichment (GAME), COPing with and CAring for infants with special needs (COPCA), and constraint-induced movement therapy for infants (Baby-CIMT), when compared to standard care, conventional interventions, or massage. Conclusion: The main components identified included task-specific motor training, associated with parent coaching and enrichment strategies, implemented on a daily basis in the infant’s home environment.